Functional and Anatomical Brain Abnormalities and Effects of Antidepressant in Major Depressive Disorder. Issue 5 (September 2015) - Fang, Junfang; Mao, Ning; Jiang, Xingyue; Li, Xuri; Wang, Bin; Wang, Qian
<x xml:space="preserve">Abstract</x> Objective Convergent studies suggest that functional and morphological abnormalities of the brain circuits may contribute to the pathophysiology of major depressive disorders (MDD). However, few study has been conducted to examine how or whether functional abnormalities are related to anatomical alterations in the brain. We used voxel-based morphometry and amplitude of frequency fluctuation (ALFF) methods to investigate their association. Methods Twenty MDD participants, 16 treated MDD participants and 18 healthy controls acquired baseline high-resolution structural magnetic resonance imaging and functional magnetic resonance imaging scans. Using SPM8 and REST1.8 software to analyze the imaging data. Results The MDDs had decreased gray matter volume and ALFF values in different brain regions. Compared to pretreatment, posttreatment MDDs had increased gray matter volume and ALFF values in some brain regions. Conclusions There is no overlap of brain regions with the functional and anatomical alterations, and they may alter independently in MDDs.